Organizational, User, and System Factors Influencing the Adoption of Electronic Medical Record Systems: A Literaturre Review - Rossa Hasbella; Elsye Maria Rosa; Lisa Musharyanti (Jurnal Ners, 2026)
The adoption of Electronic Medical Record systems has become a strategic priority in healthcare organizations to improve service quality, patient safety, and continuity of care. Despite widespread implementation efforts, adoption among healthcare professionals particularly nurses remains inconsistent and influenced by multiple interrelated factors. The purpose of this review of the literature was to compile data on organizational, user-related, and system-level factors that affect healthcare professionals' adoption and use of EMR systems. Using a qualitative meta-aggregation approach and the Joanna Briggs Institute (JBI) methodology. Studies published between 2021 and 2025 were found by searching the PubMed, Scopus, and Emerald databases. JBI SUMARI was used to critically evaluate and synthesize four papers that satisfied the inclusion criteria. EMR adoption is a multidimensional process requiring integrated organizational commitment, continuous capacity building, and system optimization. Addressing these factors is essential to enhance successful EMR implementation and sustainable use in healthcare practice.